Obraz kapłana w wypowiedziach wybranych grup katechizowanej młodzieży (studium porównawcze) - Zellma, Anna (Studia Pastoralne, 2026)
In the Year for Priests, it is the person of a priest that arouses the interest of theologians, sociologists and publicists. The following article aims to present the opinions of catechized youth from two randomly selected secondary schools (in Olsztyn and in Wodzisław Śląski). The data collected in diagnostic research have a preliminary diagnostic value since they only describe the tendencies related to the youth’s perception of the priest and attitudes to the tasks and function performed by the priest not only in the Church but also in teenagers’ lives. It was noted that opinions of respondents from Olsztyn and Wodzisław Śląski were fairly similar. Occasionally, different attitudes were observed but only in the case of some specific categories. The students’ answers were in line with the teachings of the Church. An influence of social opinion was also noticed. The views on religious education proved surprising. Negative opinions prevailed; many students stressed that religious education did not reflect the truth about priestly vocation. Apart from that, regardless of the school type and place of residence, the students suggested that more discussions on priesthood be introduced, alongside with organizing meetingswith priests and presenting audiovisual materials depicting priests devoted to God and man. Moreover, they expected testimony of faith on the part of priests and their readiness to serve and help other people.